Multiple origins of green coloration in frogs mediated by a novel biliverdin-binding serpin - Taboada, Carlos Alberto (2020)
Many vertebrates have distinctive blue-green bones and other tissues due to unusually high biliverdin concentrations—a phenomenon called chlorosis. Despite its prevalence, the biochemical basis, biology, and evolution of chlorosis are poorly understood. In this study, we show that the occurrence of high biliverdin in anurans (frogs and toads) has evolved multiple times during their evolutionary history, and relies on the same mechanism—the presence of a class of serpin family proteins that bind biliverdin. Using a diverse combination of techniques, we purified these serpins from several species of nonmodel treefrogs and developed a pipeline that allowed us to assemble their complete amino acid and nucleotide sequences. The described proteins, hereafter named biliverdinbinding serpins (BBS), have absorption spectra that mimic those of phytochromes and bacteriophytochromes. Our models showed that physiological concentration of BBSs fine-tune the color of the animals, providing the physiological basis for crypsis in green foliage even under near-infrared light. Additionally, we found that these BBSs are most similar to human glycoprotein alpha-1-antitrypsin, but with a remarkable functional diversification. Our results present molecular and functional evidence of recurrent evolution of chlorosis, describe a biliverdin-binding protein in vertebrates, and introduce a function for a member of the serpin superfamily, the largest and most ubiquitous group of protease inhibitors.